2016
DOI: 10.1007/s12032-016-0737-9
|View full text |Cite
|
Sign up to set email alerts
|

Peptide receptor radionuclide therapy for metastatic paragangliomas

Abstract: There is little evidence to direct the management of malignant paragangliomas (mPGL) beyond initial surgical treatment. Peptide receptor radionuclide therapy (PRRT), using somatostatin analogues, is effective in other neuroendocrine tumours, but data on its efficacy in treating mPGL are scarce. We report safety and efficacy outcomes from a case series of five patients with advanced mPGLs treated with (177)Lu-DOTATATE PRRT. The mean age of our cohort was 34 years (range 16-47); 4 patients were male with bone di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…SSTR overexpression in PPGL led to their use as therapeutic targets. By attaching radionuclides ( 177 Lu, 90 Y, 111 In) via a linker and vector mechanism to a targeting moiety (DOTATATE, DOTANOC, DOTATOC), PRRT has been studied in well-differentiated, advanced neuroendocrine tumors (NETs) (83)(84)(85)(86)(87). While overall results have varied, the majority of studies report the feasibility, effectiveness, and efficacy of PRRT in NETs (84,87), with increased progression free survival (PFS), as well as patient reported pain relief, symptom regression, and increased quality of life (83).…”
Section: Radionuclide Therapymentioning
confidence: 99%
“…SSTR overexpression in PPGL led to their use as therapeutic targets. By attaching radionuclides ( 177 Lu, 90 Y, 111 In) via a linker and vector mechanism to a targeting moiety (DOTATATE, DOTANOC, DOTATOC), PRRT has been studied in well-differentiated, advanced neuroendocrine tumors (NETs) (83)(84)(85)(86)(87). While overall results have varied, the majority of studies report the feasibility, effectiveness, and efficacy of PRRT in NETs (84,87), with increased progression free survival (PFS), as well as patient reported pain relief, symptom regression, and increased quality of life (83).…”
Section: Radionuclide Therapymentioning
confidence: 99%
“…Though the experience with PRRT is predominantly limited to gastroenteropancreatic neuroendocrine tumours, few studies have also evaluated its efficacy and safety in PPGLs . However, the individual studies have been conducted with limited number of patients and the precise effect of PRRT in treatment of advanced PPGLs is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported significant therapeutic responses and increased progression free survival in patients with various neuroendocrine tumors, including metastatic PHEO/PGL, undergoing PRRT [6,[10][11][12][13][14][15]. Currently, PRRT is performed according to different protocols: a combination of 90 Y-DOTATOC and 177 Lu-DOTATOC or monotherapy with 1 77 Lu-DOTATATE.…”
Section: Discussionmentioning
confidence: 99%